Stress Analysis of Solar Electric Bus Chassis Using Finite Element Method - Alief Wikarta; Yolas Aditya Yudha (JMES The International Journal of Mechanical Engineering and Sciences, 2020)
All of the electrical and mechanical components in the solar-electric bus certainly require a chassis. A chassis frame construction must be strong and light enough to bend when it receives loads. This article focuses on stress analysis using finite element method related to the solar-electric bus chassis, including the vertical load, longitudinal (acceleration and braking), and turning load. It began with a literature review and collecting the data of chassis dimensions and materials. It was then ended by getting the data simulation and evaluation of comparison results. From the simulation results for the chassis initial design, the highest Von-Misses stress happened for turning load, 182.45 MPa, and a safety factor of 1.4. While from simulation of the redesigned chassis, the Von-Mises stress reduced to 169.87 MPa with a safety factor of 1.5. Furthermore, the vertical load conditions resulted in the lowest Von-Mises stress, which was 87.89 MPa with a safety factor of 2.84.